Is Corporate Governance Priced at Stock Market? An Evidence from Nepalese Listed Firms - Ghimire, Sanjay (PYC Nepal Journal of Management, 2010)
This paper is originally presented at the “International Seminar on Management” on “Enhancing Enterprise Effectiveness for Global Challenges” organised by Brihaspati College, Siddharthnagar on 3rd and 4th April 2010. The author acknowledges that the printed version of the paper has come after the suggestions from the Editorial Committee. The study addresses the question whether ‘good’ corporate governance has a positive impact on firm valuation. Here, investigation is made using a broad sample of listed Nepalese firms. To provide a comprehensive analysis, the study use a broad corporate governance index and two additional governance mechanisms: ownership concentration and leverage. To avoid incorrect inferences due to possible endogenous relationships between the different governance mechanisms themselves as well as between the governance mechanisms and value, equations are estimated in a system of simultaneous equations using three-stage least square approach. The result supports the widespread hypothesis – a positive relationship between firm-specific corporate governance and firm value.